EVALUATION OF POTENTIAL OF HYDROGEN (PH) OF SODIUM HYPOCHLORITE AT THREE DIFFERENT MOMENTS BEFORE ITS EXPIRATION DATE - dos Santos Pereira, Sarah Regina; Pereira , Thaís Cristine; Meccatti, Vanessa Marques; de Carvalho , Lara Steffany; Coser Bridi, Enrico; de Oliveira, Luciane Dias; Abu Hasna, Amjad (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
Sodium hypochlorite (NaOCl) is the most common used irrigant for root canal treatment, it was introduced into endodontics in the last half of XVIII century. the aim of this study was to evaluate the pH stability of sodium hypochlorite (of different concentrations) and saline solution at three different moments. The pH of the irrigants was measured in triplicate using a pH meter Mettler Toledo SevenEasy S20 (Mettler-Toledo AG. Analytical Instruments. Schwerzenbach, Switzerland) at three moments: S1: upon unpacking the solution bottle; S2: one month later; and S3: four months later. Data were submitted to normality tests. Then were analyzed by One-way Anova and Tukey tests by GraphPad Prism 6 (La Jolla, CA, USA) with a significance level of 5%.   It was found that there was a statistically significant difference among the Sodium hypochlorite 1% and 2.5% in comparison with the saline solution and distilled water groups in S1, S2 and S3. Besides, it was found that sodium hypochlorite 1% loses its alkaline pH since the first month. However, sodium hypochlorite 2.5% was more stable after 4 months. It was concluded that The storage time has an effect on 1% sodium hypochlorite pH stability.